Existence of a sharp transition in the peak propulsive efficiency of a low-Re pitching foil. (7th July 2016) - Das, Anil; Shukla, Ratnesh K.; Govardhan, Raghuraman N.
Abstract : We perform a comprehensive characterization of the propulsive performance of a thrust generating pitching foil over a wide range of Reynolds ( 10Re2000 ) and Strouhal ( St ) numbers using a high-resolution viscous vortex particle method. For a given Re, we show that the mean thrust coefficient C_T increases monotonically with St, exhibiting a sharp rise as the location of the inception of the wake asymmetry shifts towards the trailing edge. As a result, the propulsive efficiency too rises steeply before attaining a maximum and eventually declining at an asymptotic rate that is consistent with the inertial scalings of St^2 for C_T and St^3 for the mean power coefficient, with the latter scaling holding, quite remarkably, over the entire range of Re . We find the existence of a sharp increase in the peak propulsive efficiency η_max (at a given Re ) in the Re range of 50 to approximately 1000, with η_max increasing rapidly from about 1.7 % to the saturated asymptotic value of approximately 16 % . The St at which η_max is attained decreases progressively with Re towards an asymptotic limit of 0.45 and always exceeds the one for transition from a reverse von Kármán to a deflected wake. Moreover, the drag-to-thrust transition occurs at a Strouhal number St_tr that exceeds the one for von Kármán to reverse von Kármán transition. The St_tr and the corresponding power coefficient C_p, _tr are found to be remarkably consistent with the simple scaling relationships St_trRe^-0.37 and C_p, _trRe^-1.12 that are derived from a balance of the thrust generated from the pitching motion and the drag force arising out of viscous resistance to the foil motion. The fact that the peak propulsive efficiency degrades appreciably only below Re≈ 10^3 establishes a sharp lower threshold for energetically efficient thrust generation from a pitching foil. Our findings should be generalizable to other thrust-producing flapping foil configurations and should aid in establishing the link between wake patterns and energetic cost of thrust production in similar systems.